New Universal Current-Mode Filter Using Non-Inverting Second-Generation Current-Conveyors - Muhammad Taher Abuelma'atti; Aamir Alam Farooqui (Active and Passive Electronic Components)
A new universal active current-mode filter with single input and five outputs is presented. The proposed filter avoids the use of feedback in any part of the circuit and uses only one type of second-generation current-conveyors, grounded resistors, and grounded capacitors. The proposed circuit can simultaneously realize lowpass, highpass, bandpass, allpass, and notch biquadratic filter functions.